Meningkatkan Aktivitas, Motivasi, dan Hasil Belajar Muatan IPA Menggunakan Kombinasi Model Problem Based Learning, Teams Games Tournament, Course Review Horay pada Siswa Kelas IV SDN 2 Pagat Hulu Sungai Tengah - Suhaimi; Ine Anisa Fitri (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem lies in the low level of activity, motivation and student learning outcomes in science content. The aim of this research is describe educators' activities, analyze student activities, motivation and learning outcomes. The research approach use qualitative with PTK research type which he carried out in 4 findings for the object studied who were class IV (four) students at SDN 2 Pagat Hulu Sungai Tengah. From these findings, the results of educators' activities have increased by getting a score of 100 on the amazingly criteria. Student activity increased to 100% of the criteria for All Active Students. Motivation to learn also increased to 100% Very High criteria. Student learning outcomes increase to 100% of the criteria for all students to complete. Based on research findings, it can be concluded that the use of a combination of Problem Based Learning (PBL), Teams Games Tournament (TGT), and Course Review Horary (CRH) models is able to increase student activity, motivation and learning outcomes well.